INVESTIGATING THE POTENTIAL OF SILYMARIN AND/OR SPIRULINA PLATENSIS TO ATTENUATE THE DELETERIOUS CONSEQUENCES OF AFLATOXIN CONTAMINATION IN BROILERS’ FEEDS - Reda A. Hassan; Zeinab M. Farouk; Bahaa Abou-Shehema; Ali El-Shafey; Youssef A. Attia; Rashed A. Alhotan; Nicola F. Addeo; Fulvia Bovera; Maria C. de Olivera (Journal of Animal and Plant Sciences, 2024)
The aim of this investigation was to establish the impact of silymarin and/or Spirulina platensis in mitigating the adverse effects of aflatoxin (AF) present in poultry feed. A total of 450 one-day-old, unsexed Ross 308 broiler chicks were allocated to a completely randomized design with five experimental groups. Each group consisted of six replicate, housing 15 chicks per replicate. The treatment groups comprised: 1) the negative control (NC) fed the standard diet lacking AF supplementation; 2) the positive control (PC) fed the standard diet contaminated with 1 mg AF/kg; 3) the silymarin (SIL) fed the PC diet + 0.6 g silymarin/kg feed; 4) the Spirulina platensis (SP) fed the PC diet + 1g /kg diet; 5) the silymarin +Spirulina fed the PC diet + 0.6 g SIL/kg + 1g SP/kg diet. Productive performance, serum biochemical profile (levels of AST, ALT, total cholesterol, HDL, uric acid, creatinine, and calcium), weight of lymphoid organs, levels of glutathione and malonaldehyde in the liver, antibody titers against NDV and IBD, concentration of cecal bacteria, nutrition composition of flesh, and level of remnants of AF in liver and flesh were studied. Our findings revealed a successful reversal of adverse effects caused by AF. Supplementation with either SIL and/or SP restored performance metrics to the levels observed in the non-contaminated (NC) fed control group. These results indicate that dietary inclusion of 0.6 g of SIL/kg and/or 1 g of SP/kg represents a suitable strategy to maintain broiler growth performance, immune function, serum composition, and meat quality in birds exposed to AF contamination at a concentration of 1 mg/kg of feed.
Keywords: aflatoxicosis; silymarin; Spirulina platensis; poultry; productive performance